Determination of amphetamine and methadone in human urine by microextraction by packed sorbent coupled directly to mass spectrometry: An alternative for rapid clinical and forensic analysis†. Issue 22 (30th September 2014) - Vlčková, Hana; El‐Beqqali, Aziza; Nováková, Lucie; Solich, Petr; Abdel‐Rehim, Mohamed
<x xml:space="preserve">Abstract</x> Speed and low cost, together with regulatory approval, are the most important requirements of clinical assays. Therefore, a fast and automated on‐line sample preparation method is essential for the routine analysis of biological samples. Microextraction by packed sorbent is an option for optimal sample preparation due to its easy automation, minimal requirements for the sample and elution solvent volumes, elimination of evaporation and reconstitution steps, and ability to integrate sample preparation and injection into one step. The use of effective sample preparation steps circumvents the need for chromatographic separation and therefore allows more rapid and less expensive sample analysis in clinical and forensic practice. Two biologically active compounds, amphetamine and methadone, were chosen as representative drugs of abuse for the application of microextraction by packed sorbent coupled directly to mass spectrometry. The developed method was validated, with the results confirming the suitability of the combination of these techniques for the analysis of biological samples. The approach was confirmed to be appropriate for use in clinical and forensic practice with regard to cost and time requirements for analysis.